ANTIMICROBIAL EFFECTIVENESS OF CALCIUM HYDROXIDE, PROPOLIS, AND THEIR COMBINATION ON THE GROWTH OF Streptococcus mutans - Mahdi, LM Fachry Ramadhani; Prastyo, Alfian Nur; Adiningrat, Arya (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Dental caries is a global oral health issue associated with the dominance of Streptococcus mutans in dental plaque. Calcium hydroxide is a commonly used dental material; however, there are increasing concerns regarding its adhesion and dissolution issues. Propolis, a natural compound with antimicrobial properties, promotes fibroblast proliferation, releases antioxidants, and reduces oxidative stress when combined with calcium hydroxide. This combination shows potential for enhancing antibacterial efficacy and pulp preservation in restorative dentistry. Purpose: This study aims to evaluate the antimicrobial effect of a combination of calcium hydroxide and propolis in inhibiting the growth of Streptococcus mutans. Methods: The experimental study assessed the antimicrobial activity of Streptococcus mutans ATCC 25175 using the agar disk-diffusion method. Five treatments with five repetition groups were tested: 2% chlorhexidine (positive control), propolis, calcium hydroxide, a calcium hydroxide-propolis mixture, and saline (negative control). The inhibition zone was measured after 24 hours of incubation at 37°C. Data were analyzed using one-way ANOVA and Tukey's post hoc test in IBM SPSS 25. Results: The positive control (chlorhexidine) showed the largest inhibitory zone (1.488±0.11), followed by propolis (0.862±0.06), calcium hydroxide combined with propolis (0.746±0.05), and calcium hydroxide suspension which suggested the smallest inhibitory zone (0.684±0.09). Conclusion: The combination of calcium hydroxide and propolis demonstrated superior antibacterial activity against Streptococcus mutans only when compared to calcium hydroxide suspension alone.